Circular Economy as a Postulate of Non-Financial Reporting in the SME Sector - Katarzyna CHŁAPEK; Sylwia KRAJEWSKA (Communications of International Proceedings, 2021)
In accordance with applicable legal regulations, disclosure of non-financial information is an obligation imposed on public interest entities and large companies. It mainly applies to non-financial key performance indicators and information on employee issues and the natural environment. The listed companies cooperate with enterprises from the SME sector, and it is not possible to apply adequate regulations regarding non-financial reports without participation of micro, small and medium-sized enterprises in this process. The only solution that enables the achievement of the goals underlying applicable laws is to require that non-financial reporting applies to the entire production chain, in line with the idea of ​​a circular economy which includes all stages of product's life cycle, starting with its design, production, consumption, up to waste collection and its management. The purpose of the article is to identify the need for non-financial reporting in micro, small and medium-sized enterprises in Poland in the aspect of circular economy. The research method includes the study of the regulations on non-financial reporting, the review of domestic and foreign literature, as well as analysis of the report published by the European Federation of Accountants and Auditors for SMEs on Survey of Non-Financial Reporting Requirements for SMEs in Europe. The summary includes recommendations for micro, small and medium-sized enterprises in Poland and an incentive to develop further research in this area having regard to the fact that micro, small and medium-sized enterprises have a great impact on achieving the goals of sustainable development in large companies.
Keywords: Non-financial reporting; SME sector; circular economy; EFAA report